Editors’ Introduction - Goulding, Marc; Meade, Teresa; Power, Margaret (Radical history review, 2023)
This essay explores several key themes regarding political imprisonment and confinement. Neither governments nor activists agree on who is and who is not a political prisoner. Governments routinely deny they imprison people for political reasons. Instead, they consistently seek to criminalize those they detain as part of their effort to maintain the legitimacy of their rule and delegitimize those who act against it. A common definition of who is and who is not a political prisoner does not exist among prisoners, activists, or supporters. No international organizations or national bodies have developed a shared description of what constitutes a political prisoner. Instead, as this essay and the articles that follow illustrate, the subject is a matter of debate and discussion.